(Invited) The Interplay of Conformation and Electronic Structure in Metal Organic Frameworks. (8th September 2020) - Pramudya, Yohanes; Kozlowska, Mariana; Heidrich, Shahriar; Krstić, Marjan; Haldar, Ritesh; Neumann, Tobias; Schlöder, Tobias; Zhang, Qiang; Symalla, Franz; Hassan, Zeinab Mohamed; Liu, Xiaojing; Heinke, Lars; et al.
Abstract : Metal organic frameworks (MOFs) are a fascinating class of materials that is currently investigated in the context of many applications. The large size of the chemical space of these systems, comprising organic linkers connected by metal centers, precludes an exhaustive experimental search for optimal materials. For this reason, a variety of modeling tools, ranging from structure-generators to electronic structure methods has been applied to understand and increasingly predict their function. Here we review some recent studies, where computational methods were used to elucidate MOF properties, such as electroluminescence, refraction index, and charge transports. As these methods become more predictive, they enable computational screening of MOF materials.